2014
DOI: 10.1073/pnas.1323112111
|View full text |Cite
|
Sign up to set email alerts
|

Ca v 3.2 T-type calcium channel is required for the NFAT-dependent Sox9 expression in tracheal cartilage

Abstract: Significance The tracheal cartilage rings are important for protecting and maintaining the airway. However, the chondrogenesis of tracheal cartilage is not completely understood. We demonstrate that the Ca v 3.2 T-type calcium channel is required for normal tracheal cartilage ring formation. Calcium influx via Ca v 3.2 induces chondrogenesis and up-regulates a chondrogenic master gene, sex determination region of Y chromosome (SRY)-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 88 publications
3
37
0
Order By: Relevance
“…It is interesting that our chondrocyte Bmal1-cKO mice showed profound and progressive lesions in the articular cartilage that were not found in global Bmal1-KO mice (22). The articular cartilage was reportedly normal in global Bmal1-KO Consistent with earlier reports on NFAT-mediated regulation of Sox9 (35,36), protein levels of SOX9 were concomitantly reduced in cKO knee cartilage ( Figure 6, B and C). Significant reductions of Sox9, Acan, and Col2a1 mRNA in cKO cartilage were observed at the 2 night time points ( Figure 6D).…”
Section: Discussionsupporting
confidence: 89%
“…It is interesting that our chondrocyte Bmal1-cKO mice showed profound and progressive lesions in the articular cartilage that were not found in global Bmal1-KO mice (22). The articular cartilage was reportedly normal in global Bmal1-KO Consistent with earlier reports on NFAT-mediated regulation of Sox9 (35,36), protein levels of SOX9 were concomitantly reduced in cKO knee cartilage ( Figure 6, B and C). Significant reductions of Sox9, Acan, and Col2a1 mRNA in cKO cartilage were observed at the 2 night time points ( Figure 6D).…”
Section: Discussionsupporting
confidence: 89%
“…As mentioned before, the T-type CaV3.2 was the first VDCC shown to be indispensable for tracheal chondrogenesis both in vivo and in vitro [40]. These findings were substantiated by the fact that mice lacking CaV3.2 showed congenital tracheal stenosis; conversely, Cav3.2 over-expression in ATDC5 cells augmented chondrogenesis.…”
Section: Vdccs Are Required For Chondrogenesismentioning
confidence: 54%
“…Although the above studies showed the presence of functional α1 subunits in mature or differentiating chondrocytes, CaV3.2 was the first α1 subunit identified as essential for tracheal chondrogenesis in mice; in mice lacking CaV3.2 channels, Sox9 expression was attenuated, accompanied by disturbed tracheal cartilage formation [40].…”
Section: Subunit-specific Expression Of Vdcc: α1 Subunitsmentioning
confidence: 96%
“…The identification of Sox9 as a direct target gene of NFATc1 in pancreatic carcinogenesis is also supported by results from a recently published genome-wide ChIP-Seq analysis showing a recruitment of NFATc1 to the Sox9 promoter in primary pancreatic tumor cells derived from Kras G12D ;NFATc1 mice 22 . The activation of the NFATc1-Sox9 axis is not restricted to epithelial regeneration or cancer initiation since recent work identified NFATc1 recruitment to the Sox9 promoter during tracheal cartilage development 47 .…”
Section: Discussionmentioning
confidence: 99%